Kisspeptin and Cancer: Molecular Interaction, Biological Functions, and Future Perspectives - Ciaramella, Vincenza; Della Corte, Carminia Maria; Ciardiello, Fortunato; Morgillo, Floriana (Frontiers in Endocrinology, 2018)
Cancer disease is the second leading cause of death in the world and one of the main fields of medical research. Although there is now a greater understanding of biological mechanisms of uncontrolled cell growth, invasiveness and metastasization, the multi-step process of cancer development and evolution is still uncompletely understood. The inhibition of molecules activated in cancer metastasization is an hot topic in cancer research. Among the known anti-metastatic genes, KiSS-1 is involved in the metastatic cascade by preventing growth of metastasis. Moreover, loss of KiSS-1 protein expression by tumor cells has been associated with a more aggressive phenotype. KiSS-1 gene encodes a 145 amino acid protein which, following proteolytic cleavage, generates a family of kisspeptins, (Kp-10, -13, -14), that are endogenous agonists for the G-protein coupled receptor, GPR54. The anti-tumour effect of KiSS-1 was primarily associated with the inhibition of proliferation, migration and cell invasion and, consequently, the reduced formation of metastasis and intratumoural microvessels. In this review, we highlight the latest data on the role of the kisspeptin signalling in the suppression of metastasis in various cancer types and the use modulators of KiSS/GPR54 signalling as potential novel therapeutic agents for the treatment of cancer.